Analysis of Marketing Strategy and Market Potential in the Development of MUA Business in the Digital Era: A Sharia Economic Perspective (Case Study of Rahma Mansyur, MUA Kolaka) - Febyola Febyola; ⁠ Abd. Rizal; ⁠ Jumasrah ⁠ Jumasrah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze marketing strategies and market potential in the development of Makeup Artist (MUA) businesses in the digital era from an Islamic economic perspective, with a case study of Rahma Mansyur MUA in Kolaka. The research method applied is descriptive qualitative, utilizing interviews, observations, and documentation. The findings reveal that digital marketing strategies through social media, customer testimonials, and collaborations with wedding vendors play a crucial role in increasing visibility and consumer trust. Furthermore, the market potential for MUA services continues to grow along with the rising demand for beauty services in weddings, graduations, and other formal events. From an Islamic economic perspective, Rahma Mansyur MUA’s marketing practices reflect honesty, transparency, and adherence to Islamic ethical values in transactions. This study concludes that digital-based marketing strategies integrated with sharia principles can enhance competitiveness and expand market share for MUAs in the modern era.